Exploring Potential Aquaculture-Immunostimulant-Peptides Derived from Chlorella sorokiniana - Safitri, Nur Maulida; Violando, Wiga Alif; Suhermanto, Achmad; Rizkiah, Riza; Mukhaimin, Iman; Ramli, Taufik Hadi; Puspitasari, Asthervina Widyastami; Zummah, Atiqoh (Jurnal Biologi Tropis, 2024)
Chlorella sorokiniana is a microalgae with an outstanding nutritional profile and numerous therapeutic substances that can be used as an immunostimulant, including in aquaculture. This research aimed to investigate and characterize peptides isolated from C. sorokiniana protein using TCA digestion and hydrolyzed enzymatically with trypsin. Peptides were then subsequently identified using Tandem LC-MS/MS and Mascot Distiller. Results showed that the percentage of pure protein yield following TCA digestion was 54.66%, and 12 peptides with lengths ranging from 7 to 23 sequences were discovered after trypsin digestion. These peptides originated from various enzymes and chloroplast proteins, including protein synthesis elongation factor TU, photosystem I iron-sulfur center, photosystem II 43 kDa, Ycf4, ATP-dependent zinc metalloprotease FtsH homolog, nitrate reductase, chloroplastic glucose-6-phospate dehydrogenase, and ATP synthase CF1 alpha chain. These findings demonstrated that C. sorokiniana might serve as a source of immunostimulant peptides and proteins, particularly for aquaculture biota.